The Role of the Audit Committee and Board of Directors in Assessing the Performance and Effectiveness of Internal Audit (Case Study at PT APS) - Hasan (Cv. Syntax Corporation Indonesia, 2026)
This study analyzes the role of the Audit Committee and the Board of Directors in assessing the performance and effectiveness of internal audit at PT APS, considering the coordination mechanism as a mediator and contextual factors as moderators. Strengthening the internal audit function in state-owned enterprises (SOEs) is critical for supporting good corporate governance. The objectives are to examine the influence of the roles of the Board of Directors and the Audit Committee on internal audit effectiveness, assess the coordination mechanism, and identify moderating contextual factors, while also providing practical recommendations for PT APS and other SOEs. The study employs a quantitative approach with an explanatory research design, using SEM-PLS analysis via SmartPLS 4.0 software. A cross-sectional survey method is applied with a sample of 30 respondents. The results indicate that all variables have high average values, with the Role and Support of the Board of Directors showing the highest score (4.25). The effectiveness of the Audit Committee, the Coordination Mechanism, and Internal Audit Performance were also assessed positively, while the Contextual Factor had a slightly lower average (3.98). The findings show that the commitment of the Board of Directors and the Audit Committee significantly enhances internal audit effectiveness. A strong coordination mechanism plays a crucial role, although contextual factors require greater attention. Recommendations include formalizing the coordination charter, developing specialized competencies, and establishing a technology roadmap to strengthen internal audit, as well as offering guidance for other SOEs and regulators.